Code-Mixing of Indonesian and English on Instagram Social Media - Zebua, Yuniati; Munthe, Lince; Manik, Sondang; Edi Suprayetno (English Lecturers and Teachers Association (ELTA), 2025)
Code-mixing, the practice of alternating between two or more languages within a single discourse, became increasingly prevalent in digital communication, particularly on social media platforms like Instagram. This study investigated the patterns of code-mixing in Instagram posts, captions, and comments, focusing on the combination of Indonesian and English. The research aimed to identify the linguistic patterns and explore the social, cultural, and psychological factors influencing users' language choices. Additionally, the study examined the impact of code-mixing on user comprehension and interaction, particularly in terms of audience engagement and communication effectiveness. Data were collected from a sample of Instagram posts and analyzed using a qualitative approach, focusing on instances of code-mixing and the context in which it occurred. The findings revealed that code-mixing served multiple purposes, including emphasizing certain messages, expressing identity, and engaging with a broader audience. Moreover, the study found that while code-mixing enhanced interaction and facilitated communication, it also posed challenges in terms of clarity and accessibility for some users. The research concluded that code-mixing was a dynamic feature of digital communication, shaped by social factors and user intent. Understanding these patterns could inform the development of more inclusive and effective communication strategies in online environments. Keywords : code-mixing, social media, Instagram, language patterns